A Study on the Success Strategies of Chinese Aerial Work Platform Manufacturers in the Korean Market: Focusing on the Case of Dingli (aSSIST Business Review, 2026)
Background/Purpose: The Korean Aerial Work Platform (AWP) market has grown significantly since the 1990s, driven by demands for improved safety and efficiency in construction and industrial sectors. Chinese manufacturers, particularly Dingli, have disrupted this market. This study examines how Dingli achieved market leadership in Korea, providing strategic insights for global firms entering competitive markets. Study Design/Methodology/Approach: This is a qualitative case study analyzing Dingli's Korean market entry and growth strategy through the lens of the 4P marketing mix framework (Product, Price, Place, Promotion). Data were gathered through industry reports, market data from the Association of Equipment Manufacturers (AEM), and secondary sources covering the period 2016–2024. Findings: Dingli entered the Korean market in 2016 but initially struggled due to quality concerns. Following the COVID-19 pandemic, the company implemented aggressive marketing, improved product quality, established local inventory, and offered flexible payment terms. By 2023, Dingli achieved a 29% market share, surpassing established North American manufacturers. Originality/Value: This study provides a comprehensive 4P analysis of a Chinese manufacturer's successful penetration of a mature, competitive market previously dominated by premium Western brands. The findings offer actionable lessons for global companies seeking to enter the Korean market or similar competitive environments.
Keywords: Aerial Work Platform; Korean market entry; Dingli; 4P marketing mix; Chinese manufacturer; market strategy